Sacred and Cultural Awareness: Philosophical and Religious Values of the Tanggai Dance in the Context of Palembang Malay Tradition, Indonesia - Agustina, Halimah; Malarsih, Malarsih; Sugiarto, Eko (Journal of Education Culture and Society, 2026)
Aim. This study aims to explore and interpret the philosophical and religious values contained in the Tanggai Dance as a representation of Palembang Malay identity in Indonesia, which in the categories functions as an aesthetic vessel, ethical tool, and religious medium.Methods. The research method used is a case study with an interdisciplinary approach, data collected through literature review, field observations, and in-depth interviews with dance artists, maestros, traditional leaders, and the younger generation. Data analysis uses a combined paradigm: movement semiotics for sign mapping, performativity theory for understanding reproducible norms, and body phenomenology for interpreting embodied experiences.Results. The meaning in Tanggai Dance is relational and multi-layered: formation patterns, subtle hand movements, repetitive rhythms, and props (golden nails) interact to form a symbolic system that functions aesthetically, ethically, and religiously. Repetition of practice and performance becomes the primary medium for internalizing values; the studio as a community of practice reproduces meaning through imitation, narrative, and sensory experience. Cross-generational results show that the negotiation of meaning in which the older generation maintains a sacred nuance, while the younger generation emphasizes aesthetic aspects-mediated by changes in modes of bodily experience and performance context.Conclusions. The findings indicate that Tanggai dance not only serves as a religious and ceremonial expression, but also has significant potential as a pedagogical medium for teaching local wisdom, strengthening cultural identity, and revitalizing dancers engagement with traditional arts as young people in contemporary times. This study recommends a dance curriculum based on embodied reflection, multimodal documentation, and standardized intergenerational programs to ensure the continuity of philosophical and religious meanings in cultural preservation.